Influence of socioeconomic status on changes in body size and physical activity in ageing black South African women - Gradidge, Philippe Jean-Luc; Norris, Shane A.; Munthali, Richard; Crowther, Nigel J. (BioMed Central, 2018)
Background: The increasing prevalence of obesity in sub-Saharan African women is not well understood, and black South African women in the region are particularly vulnerable. This study aimed to examine whether the relationship of socioeconomic status (SES) with changes in body mass index (BMI) and waist circumference (WC) is mediated by physical activity in ageing African women. Methods: In a longitudinal analysis of the 518 caregivers associated with the Birth to Twenty Plus study, the role of SES associated with 10-year changes in BMI and WC was tested using structural equation modelling (SEM). The degree of mediation of moderate-vigorous physical activity (MVPA) and sitting time in this association was also assessed. Results: The prevalence of obesity increased significantly from baseline to follow-up (p < 0.0001). In the SEM models, baseline SES had a direct positive effect on changes in BMI (β, 95% CI, 0.02 (0.005 to 0.04), and a direct negative effect on changes in MVPA (β, 95% CI, − 3.81 (− 6.92 to − 0.70). Baseline MVPA had a direct negative effect (β, 95% CI, − 0.002 (− 0.003 to − 0.0003) and indirect positive effect via change in MVPA (β, 95% CI, 0.01 (0.0001 to 0.001) on change in WC. Conclusions: Our study demonstrates the role and interaction of sociodemographic and behavioural predictors of obesity and suggests a multifaceted approach to management of the crisis in communities of ageing urban African women.
Keywords: Body mass index; Waist circumference; Socioeconomic status; Physical activity; Sitting time; Urban; African women; SDG-3: Good health and well-being